Preparation of itraconazole nanoparticles and its topical nanogel: Physicochemical properties and stability studies - Kamlesh Amrut Wadile; Pradum Pundlikrao Ige; Raju Onkar Sonawane (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2019)
The need of present study hypothesized due to drug has low bioavailability (55%) because of low aques solubility and first pass effect. Nanoparticles were prepared by solvent diffusion method by using different stabilizers such as Tween80, Pluronic F127, Sodium lauryl sulfate, span 80 and Polyvinyl alcohol. The prepared nanoparticles were characterized through particle size, polydispersity index (PDI), zeta potential, drug content, in vitro drug release study, infra-red spectroscopy, X-ray powder diffractometry and scanning electron microscopy. The optimized batch of Itraconazole nanoparticles (NF2), had particle size 167.2nm, polydispersity index 0.208, zeta potential (-17.8mV), drug content 94.8% and % cumulative drug release 86.15% ±0.5%. These prepared nanoparticles has transformed into topical nanogel. Different batches of topical nanogel were prepared like NG1, NG2 and NG3 by using Carbopol 940. All batches of topical nanogel were characterized through pH, homogeneity, spreadability, viscosity, drug content and in vitro drug release study. Based on good homogeneity, pH 6.8, viscosity (160.2 poise), spreadability (2.20 cm), drug content (77%) and cumulative drug release 85.24 ±0.9 %., NG2 batch was subjected to in vitro antifungal activity. In conclusion, prepared topical nanogel of itraconazole was stable and could be used with promising potential for fungal infection